The Comdined Effect of the Self Excited and External Forced Vibrations on the Pressure Disturbution of Short Journal Bearing. (Journal of University of Babylon for Engineering Sciences, 2018)
The performance of the journal bearing at the dynamic loading condition under the effect of self-excitation and forced harmonic excitation has been investigated. For this purpose, the conventional form of the Reynolds equation is analyzed numerically using the central finite difference technique with a proper initial and boundary condition. The numerical equations have been written in (FORTRAN-95) language to obtain the results. According to the numerical results obtained, the maximum oil pressure is obtained under the combined effect of forced harmonic vibration and self- excitation is increased by 36.66 percent from those obtained under the self- excitation only.